The Effectiveness of Personalized Marketing on Repurchase Intention in the Consumer Financing Sector: An Empirical Study from FIF - Arlien Virginia Jonathan; Billy Yonathan; Theodorus Indra Surya Putra (Journal of Business, Social and Technology, 2026)
Background: Personalized marketing strongly influences repurchase intention in Indonesia’s motorcycle financing sector, particularly at PT Federal International Finance (FIFGROUP). Objective: This study examines the impact of personalized marketing on repurchase intention, directly and indirectly through perceived relevance, perceived value, and customer satisfaction, while also exploring how customer trust can strengthen or weaken these relationships. Methods: A quantitative explanatory design was employed to evaluate the empirical validity of the hypothesized model using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through an online survey of 213 active customers who had received personalized promotions from FIFGROUP. Direct, indirect, and conditional effects were fully examined in each mediation model, with perceived relevance (PR), perceived value (PV), and customer satisfaction (CS) serving as embedded mediators, while customer trust (CT) functioned as the moderator. Results: The findings revealed that personalized marketing exerted a significant direct effect on repurchase intention (β = 0.712, p < 0.001). Indirect pathways through perceived relevance, perceived value, and customer satisfaction further amplified this relationship. Customer trust moderated these effects asymmetrically by reinforcing the effects of perceived relevance and perceived value on repurchase intention (+), while weakening the relationship between customer satisfaction and repurchase intention (−), thereby demonstrating the nuanced role of trust in personalization strategies. Conclusion: This study provides sector-specific, trust-driven, and data-driven insights from Indonesia’s two-wheeler financing industry, offering guidance for practitioners in refining personalization models and implementing marketing strategies that are relevant, value-generating, and ethically grounded to sustain long-term customer relationships.